Download as pptx, pdf, or txt
Download as pptx, pdf, or txt
You are on page 1of 31

Week 5: Boolean Algebra Part – B

Simplification Theorems
Rusdianto Roestam
2 Simplification Theorems
l
Uniting:
l
XY + XY′ = X (2-15)
l
(X + Y )(X + Y′) = X (2-15D)
l
Absorption:
l
X + XY = X (2-16)
l
X(X + Y ) = X (2-16D)
l
Elimination:
l
X + X ′Y = X + Y (2-17)
l
X(X′ + Y ) = X Y (2-17D)
l
Consensus:
l
XY + X′Z + YZ = XY + X′Z (2-18)
l
(X + Y )(X′ + Z)(Y + Z) = (X + Y )(X′ + Z) (2-18D)
3 Proof of Simplification Theorems
l
Proof of (2-15): XY + XY′ = X(Y + Y′) = X(1) = X
l
Proof of (2-16): X + XY = X · 1 + XY = X(1 + Y) = X · 1 =
X
l
Proof of (2-17): X + X′Y = (X + X′)(X + Y ) = 1(X + Y ) = X
+ Y ----- use 8D :x+yz = (x+y) (x+z)
l
Proof of (2-18): XY + X′Z + YZ = XY + X′Z + (1)YZ =
l XY + X′Z + YZ = XY + X′Z + (1)YZ =
l XY + X′Z + (X + X′)YZ = XY + XYZ + X′Z + X′YZ =
l XY + X′Z (using absorption twice – xy(1+z) + x’z(1+y))
4 Proof of (2-16D)

The other theorem can be proved using the dual
steps used to prove the first theorem.

For example, (2-16D) can be proved using the
dual steps of the (2-16) proof.

Proof of (2-16D):

X(X + Y ) = (X + 0)(X + Y ) = X + (0 · Y ) = X + 0 = X

--- use 8D :x+yz = (x+y) (x+z) and 2-16: (x+y)(x+z) = x +yz
5 Elimination theorem using switches
l
Fig (below) Its transmission is T = Y + XY′
because there is a closed circuit between the
terminals if switch Y is closed or switch X is
closed and switch Y′ is closed.
l
The following circuit is equivalent because if Y is
closed (Y = 1) both circuits have a transmission
of 1; if Y is open (Y′ = 1) both circuits have a
transmission of X.
6 Simplification of a logic gate circuit
l
In Figure below, the output of circuit (a) is
l
F = A(A′ + B)
l
By the elimination theorem, the expression for F
simplifies to AB. Therefore, circuit (a) can be
replaced with the equivalent circuit (b).
7 Example 1 - 2
l
Use absorption theorem (2-16)
l
--- Simplify Z = A′BC + A′
l if we let X = A′ and Y = BC.
l the expression simplifies to Z = X + XY = X = A′.

l Then, by the uniting theorem (2-15D), the expression


reduces to Z = X = A + B′C
8
Example 3

By the elimination theorem (2-17):


l

l
Z = X + Y = B′D + C′E′ + (AB + C)′
l Note that in this example we let X = (AB + C)′ rather
than (AB + C) in order to match the form of the
elimination theorem (2-17).
9
Theorems of Boolean Algebra
Table 2-4

l
Uniting theorems:
l
1. XY + XY′ = X 1D. (X + Y )(X + Y′) = X

l
Absorption theorems:
l
2. X + XY = X 2D. X(X + Y ) = X

Elimination theorems:
l

3. X + X′Y = X + Y 3D. X(X′ + Y ) = XY


l

l
Duality:
l
4. (X + Y + Z + · · · ) D = XYZ. . .
l
4D. (XYZ. . . ) D = X + Y + Z + · · ·

l
Theorems for multiplying out and factoring:
l
5. (X + Y )(X′ + Z ) = XZ + X′Y
l
5D. XY + X′Z = (X + Z )(X′ + Y )
l
Consensus theorems:
6. XY + YZ + X′Z = XY + X′Z
6D.(X + Y )(Y + Z )(X′ + Z ) = (X + Y )(X′ + Z )
10 Multiplying Out and Factoring
l
An expression is said to be in sum-of-products
(SOP) form when all products are the products of
single variables.
l
This form is the end result when an expression is
fully multiplied out.
l
It is usually easy to recognize a sum-of-products
expression because it consists of a sum of
product terms:
AB′ + CD′E + AC′E′ (2-19)
11 Multiplying Out and Factoring (2)
l
In degenerate cases, one or more of the product
terms may consist of a single variable.
l
For example ---- considered as SOP form:
l
ABC′ + DEFG + H (2-20)
l
A + B′ + C + D′E (2-21)
Example --- Not SOP form:
l

l
(A + B)CD + EF
l because the A + B term enters into a product but is not a single
variable.
12 Multiplying Out and Factoring (3)
l
When multiplying out an expression, apply the
second distributive law first when possible.
l
For example, to multiply out
l
(A + BC )(A + D + E ) let X = A, Y = BC, Z = D + E
l Then:
l
(X + Y)(X + Z) = X + YZ = A + BC(D + E) = A + BCD + BCE
13 Multiplying Out and Factoring (4)
the same way –- by multiplying out the original
l

expression completely and then eliminating


redundant terms:
(A + BC)(A + D + E) = A + AD + AE + ABC + BCD + BCE
= A(1 + D + E + BC) + BCD + BCE
= A + BCD + BCE
Compare to the previous way in the slide before!!!
l
14 Problem SOP (7.24)

o (a) Use gate equivalences to


convert the circuit into a four-level
circuit containing only NAND
gates and a minimum number of
inverters. (Assume the inputs are
available only in uncomplemented
form.)
o (b) Derive a minimum SOP
expression for f .
o (c) By manipulating the expression
for f , find a three-level circuit
containing only five NAND gates
and inverters.
15 Multiplying Out and Factoring (5)
l
Both distributive laws can be used to factor an
expression to obtain a product-of- sums form.
l
An expression is in product-of-sums (POS) form
when all sums are the sums of single variables.
l
It is usually easy to recognize a product-of-sums
expression since it consists of a product of sum
terms:
l
(A + B′)(C + D′ + E)(A + C′ + E′) –-------- (2-22)
16 Multiplying Out and Factoring (6)
in degenerate cases, one or more of the sum
terms may consist of a single variable. For
example,
l
(A + B)(C + D + E)F (2-23)
l
AB′C(D′ + E) (2-24)
are still considered to be in product-of-sums form, but (A
+ B)(C + D) + EF is not.
Example 1 --- how to factor using the second
distributive law: - p.49

Factor A + B′CD. This is of the form X + YZ where X = A, Y = B′, and Z = CD, so


A + B′CD = (X + Y)(X + Z) = (A + B′)(A + CD)
A + CD can be factored again using the second distributive law, so
A + B′CD = (A + B′)(A + C)(A + D)

17
Example 2

Factor AB′ + C′D.


AB′ + C′D = (AB′ + C′)(AB′ + D) ← note how X + YZ = (X + Y)(X + Z) was applied here
= (A + C′)(B′ + C′)(A + D)(B′ + D) ← the second distributive law was applied again to each term

18
Example 3
Factor C′D + C′E′ + G′H.
C′D + C′E′ + G′H = C′(D + E′) + G′H ← first apply
the ordinary distributive law,
XY + XZ = X(Y + Z)
= (C′ + G′H)((D + E′) + G′H) ← then apply the
second distributive law
19
= (C′ + G′)(C′ + H)(D + E′ + G′)(D + E′ + H) ←
now identify X, Y, and Z in each expression and
complete the factoring
20 Multiplying Out and Factoring (7)
l
An expression is fully factored iff it is in product-
of-sums form. Any expression not in this form can
be factored further.
l
The following examples illustrate how to factor
using the second distributive law:
l
Example 1: Factor A + B′CD. This is of the form X
+ YZ where X = A, Y = B′, and Z = CD, so
l
A + B′CD = (X + Y)(X + Z) = (A + B′)(A + CD)
A + CD can be factored again using the second
l

distributive law, so
l
A + B′CD = (A + B′)(A + C)(A + D)
21 Multiplying Out and Factoring (8)
l
Example 2: Factor AB′ + C′D.
l
AB′ + C′D = (AB′ + C′)(AB′ + D) ← note how X +
YZ = (X + Y)(X + Z) was applied here
l
= (A + C′)(B′ + C′)(A + D)(B′ + D) ← the second
distributive law was applied again to each term
Factor using the second distributive law
22
Example 1
Factor A + B′CD.
l

l This is of the form X + YZ where X = A, Y = B′, and Z


= CD,
l So A + B′CD = (X + Y)(X + Z) = (A + B′)(A + CD)
A + CD can be factored again using the second
l

distributive law,
So A + B′CD = (A + B′)(A + CD) =(A + B′)(A + C)(A + D)
Factor using the second distributive law
23
Example 2
l
Factor AB′ + C′D.
l
AB′ + C′D = (AB′ + C′)(AB′ + D)
l ← note how X + YZ = (X + Y)(X + Z)
was applied here
l
= (A + C′)(B′ + C′)(A + D)(B′ + D)
l ← the second distributive law was
applied again to each term
Factor using the second distributive law
24
Example 3
l
Factor C′D + C′E′ + G′H.
l
C′D + C′E′ + G′H = C′(D + E′) + G′H
l ← first apply the ordinary distributive law, XY + XZ =
X(Y + Z)
l
= (C′ + G′H)((D + E′) + G′H)
l ← then apply the second distributive law
l
= (C′ + G′)(C′ + H)(D + E′ + G′)(D + E′ + H)
l ← now identify X, Y, and Z in each expression and
complete the factoring
As in Example 3, the ordinary distributive law should be applied
l

before the second law when factoring an expression.


Circuits for
25
Equations (2-19) and (2-21)
Circuits for
26
Equations (2-22) and (2-24)
Complementing Boolean
27
Expressions
1.The inverse or complement of any Boolean
expression can easily be found by successively
applying DeMorgan’s laws.
2.DeMorgan’s laws are easily generalized to n
variables:
3.(X 1 + X 2 + X 3 + · · · + X n )′ = X 1 ′ X 2 ′ X 3 ′ . . .
X n ′ –------------>(2-25)
4.(X 1 X 2 X 3 . . . X n )′ = X 1 ′ + X 2 ′ + X 3 ′ + · · · +
X n ′ –----------->(2-26)
The inverse or complement
28
For n=3
1)(X 1 + X 2 + X 3 )′ = (X 1 + X 2 )′X′ 3 = X′ 1 X′ 2 X′ 3
2)DeMorgan’s laws can be stated as
1)The complement of the product is the sum of
the complements.
2)The complement of the sum is the product of
the complements.
3)To form the complement of an expression
containing both OR and AND operations,
DeMorgan’s laws are applied alternately.
29 Example 1
l
To find the complement of (A′ + B)C′, first apply
(2-13) and then (2-12).
l
[ (A′ + B)C′ ] ′ = (A′ + B)′ + (C′)′ = AB′ + C
l
Conversion parts:
l
- (A’ + B)’ = A’’B’ = AB’
30 Example 2
l
[(AB′ + C)D′ + E ]′ = [ (AB′ + C)D′ ]′ E′ ----- (by (2-
12))- remember (x+y)’ = x’y’
l
= [ (AB′ + C)′ + D ] E′ ---------- (by (2-13))
l
= [ (AB′)′C′ + D ] E′ ---------- (by (2-12))
l
= [ (A′ + B)C′ + D ] E′ ---------- (by (2-13)) (2-27)
l
Note that in the final expressions, the
complement operation is applied only to single
variables.
31 The inverse of F = A′B + AB′
l
F′ = (A′B + AB′)′ = (A′B)′(AB′)′ = (A + B′)(A′ + B)
l
= AA′ + AB + B′A′ + BB′ = A′B′ + AB
l
verify that this result is correct by constructing a
truth table for F and F′
l
Remember that AA’ = 1

You might also like